Strategies in Development of Iranian Medical Sciences Universities for Dynamic Presence in the International Arena - Ali-Akbar Haghdoost; Hajar Shafian; Behnam Sadeghirad; Mahasti Alizadeh; Mahmoud Reza Dehghani; Tahereh Eslaminejad; Hajar Shafian; Mahasti Alizadeh; Roqhayeh Ershad Sarabi (Kerman University of Medical Sciences, 2013)
Background & Objective: In compatibility with the progress of universities and expansion of knowledge and science around the world Iran has also had significant academic progress in recent years However the vision of Iran for the following decades is very ambitious Much has to be achieved to reach the highest position in the region in development economy science and technology This qualitative study was designed to explore the strengths and weaknesses of universities Methods: This qualitative study had three phases In the first phase we explored the topic in brain storming sessions Then the themes raised in phase one were discussed deeply in unstructured interviews with selective experts around the country In the last phase we asked 30 selective academic staff from different medical sciences universities to categorize the issues based on their importance and their solutions using Delphi method Results: Our findings showed that improvement of international affairs were frequently stressed by our respondents In this domain the English skills of academic staff and students big revision in rules and regulations and encouraging the establishment of close scientific communication with academic organizations around the world were highlighted In addition most respondents believed that problems were understandable but our main conflicts were in finding applicable solutions and implementing decisions Conclusion: Our results showed that for a better presentation of Iranian universities in the international environment a new approach to long term reform programs is necessary In this plan special attention must be paid to the educational and research infrastructures